Тенденції розвитку шкільної освіти в федеративній республіці Німеччині (1945 р. – кін. 80-х рр. ХХ ст.) - Завальнюк, Андрій; Zavalnyuk, A. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Стаття презентує тенденції розвитку шкільної освіти в Західній Німеччині від часу закінчення Другої світової війни до часу об’єднання ФРН та НДР. Розвиток шкільної освіти Федеративної Республіки Німеччини від 1945 р. до поч. 90-х рр. ХХ ст. умовно поділяємо на три етапи: 1945 р. – кін. 50-х рр. ХХ ст.; поч. 60-х рр. ХХ ст. – поч. 80-х рр.; поч. 80-х рр. – поч. 90-х рр. ХХ ст. У статті розглянуто особливості розвитку освіти післявоєнного періоду, зокрема документи, що регламентували розвиток освіти зазначеного періоду, проблеми післявоєнного періоду у функціонуванні шкіл (жахливий матеріально-технічний стан шкіл, велика кількість біженців, відсутність необхідних підручників, нестача вчителів), конфесійний розподіл населення, вирішення питання із забезпечення шкіл вчительськими кадрами, денацифікація змісту освіти, заснування шкіл різних типів та територіальний розподіл шкіл відповідно до світоглядної позиції (громадських (Gemeinschaftsschulen), християнських громадських (christliche Gemeinschaftsschulen), християнських міжконфесійних шкіл (christliche Simultanschulen), віросповідних та громадських шкіл (Bekenntnis- und Gemeinschaftsschulen), світських шкіл (Weltanschauungsschulen), атеїстичних шкіл (Bekenntnisfreie Schulen), приватних християнських шкіл); спроби та результати реформування шкільної освіти у Німеччині у період поч. 60-х рр. – поч. 80-х рр. ХХ ст.; практичне відображення положень реформ функціонування закладів шкільної освіти у період поч. 80-х рр. – поч. 90-х рр. ХХ ст. The actuality of our scientific research is determined by the necessity for the historical analysis of the school education development in Germany. This country is famous for its advantages in the field of Education, Science, and Technology; has a developed system of the school education; and is distinguished by the quality of education and upbringing. We consider that learning the positive advantages of the past, namely the experience of the German school education establishment and development in post-war time and in the period of educational reformation in the 20th century is actual nowadays. Taking into consideration the conditions in which our country is - military actions in the East part of Ukraine, a great number of the refugees, spiritual decline and despair, financial security, we think that it is more significant than ever before. It is high time to raise a question of searching new ways in the sphere of education and upbringing, to perform reforms for improving the quality of the educational and upbringing process at schools, inculcating the sense of identity, and spiritual and moral revival of the nation. Among the historical preconditions of the school confessional development in Germany in the post-war period, we underline the following ones: appalling material and technical state of the schools, lack of teachers, shortage of textbooks, a great deal of refugees. In those times, the most part of the comprehensive schools in West Germy proclaimed themselves Christian educational institutions, meanwhile in East Germany the Christian schools, both state and private, were prohibited. As a result, of the reform efforts in the late 1980s, one should recognize the general modernization of the education, orientation to the quality of education, single school recognition, enlargement of the applicants, and enlargement of the existing educational establishments.
The tendencies of the school education development in the Federal Republic of Germany (1945-in the late 1980s)
Keywords: школа; християнська школа; матеріально-технічний стан шкіл; вчителі; денацифікація; підручники; загальноосвітні школи; приватні школи; реформування освіти; school; Christian school; material and technical state of the schools; teachers; denazification; textbooks; comprehensive schools; private schools; educational reform